1976
DOI: 10.3109/inf.1976.8.issue-3.05
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Branhamella Catarrhalis (Neisseria Catarrhalis) with Special Reference to Maxillary Sinusitis

Abstract: Paired sera from 97 patients with acute maxillary sinusitis were examined regarding antibodies to Branhamella catarrhalis. Precipitating antibodies were demonstrated in almost all sera both from patients and from healthy blood donors. Complement-fixing (CF) antibodies to B. catarrhalis were present in sera from 25 of the 97 patients and in one of 20 healthy blood donors. The titres were low and the titre changes when present were of a small magnitude. CF antibodies were most commonly demonstrated in the younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Complement resistance can be considered a virulence factor of M. catarrhalis: the majority of strains (89%) isolated from lower respiratory tract infections are resistant to complement-mediated killing, whereas strains from the upper respiratory tract of children are mostly sensitive (58%) (117;Hol et al,Letter). Several other authors have tested M. catarrhalis strains for complement resistance (39,51,129,216; R. E. Winn and S. L. Morse, Abstr. 84th Annu.…”
Section: Complement Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Complement resistance can be considered a virulence factor of M. catarrhalis: the majority of strains (89%) isolated from lower respiratory tract infections are resistant to complement-mediated killing, whereas strains from the upper respiratory tract of children are mostly sensitive (58%) (117;Hol et al,Letter). Several other authors have tested M. catarrhalis strains for complement resistance (39,51,129,216; R. E. Winn and S. L. Morse, Abstr. 84th Annu.…”
Section: Complement Resistancementioning
confidence: 99%
“…Interestingly, in children with asthma, the same distribution of bacterial pathogens is found (238), although Goldenhersch et al (103) isolated M. catarrhalis as the predominant pathogen in subacute or chronic sinusitis (symptoms present for more than 30 days) in children with respiratory allergy. It has been suggested that there is a possible underestimation of isolation rates for M. catarrhalis, since the bacterium stops growing in environments with reduced oxygen concentrations, a condition frequently present during sinusitis and otitis media (39,204). This would indicate an even greater role for M. catarrhalis in the etiology of these infectious diseases.…”
Section: Sinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…However, because B. catarrhalis is distinctly different from the Moraxella spp. in cell morphology and has recently been recognized as a pathogen (21,27,68), the name B. catarrhalis is commonly used, although no formal request has been made to have the name conserved taxonomically.…”
Section: Historical Perspectives On the Taxonomy Of The Family Neissementioning
confidence: 99%
“…catarrhalis causes sinusitis in adults and children (21,95,180). The organism is recovered alone or in combination with other bacteria from direct sinus aspirates obtained from patients with clinical and radiographic evidence of acute bacterial sinusitis.…”
Section: Other Infectionsmentioning
confidence: 99%